THE PRODUCTION OF KNOWLEDGE STANDARDIZATION PRINCIPLES IN WORKS OF ARISTOTLE - Шенгерій, Л. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The analysis of Aristotle`s ideas in the context of logical and rational cognitive processes is done. The attention is stressed upon the analysis of formal principles and means of knowledge standardization.